Integrated bio- and chemo-stratigraphy for Early Cretaceous strata offshore Gabon: Additional constraints on the timing of salt deposition and rifting of the South Atlantic. (February 2023) - Eldrett, James S.; Bergman, Steven C.; Heine, Christian; Edwards, Paul; Jakeman, Marcus; Miles, Nick; Hambach, Bastian; Bohaty, Steven M.; Wilding, Megan R.
Abstract: Early Cretaceous rift basins of the incipient South Atlantic have been the focus of intense hydrocarbon exploration and production activities and host some large oil accumulations in sections predating an interval of major salt deposition, particularly in the central segment of the South Atlantic. Understanding the timing (and associated uncertainties) of source rock and reservoir deposition and their relationship with rift evolution is critical for successful exploration. However, there are still many unresolved issues and data gaps regarding the precise age and duration of salt deposition. Better chronological constraints are particularly needed to determine the timing of deposition of Pre-Salt reservoirs and the primary evaporites, as well as the secondary phase of halokinensis that resulted in variable reservoir sealing potential. To help address this gap, stable carbon isotope (δ 13 C) records from bulk organic matter and insoluble kerogen were generated for the Early Cretaceous salt and Pre-Salt intervals from two exploration wells offshore of Gabon. The bulk organic δ 13 C stratigraphies for the two wells were then integrated with palynological and ostracod biostratigraphy and placed within a sequence stratigraphic and regional tectonic framework, providing new constraints on the timing of rift lake evolution and salt deposition. The good correlation between the offshore Gabon δ 13 C record with other published sections calibrated to the current Geologic Time Scale as well as other regional sections from NE Brazil, supports the reliability of our new Gabon δ 13 C record. Several δ 13 C excursions are identified in the Pre-Salt sequence and are correlated with the Valanginian Weissert event and Early Aptian δ 13 C event(s). Salt deposition on the Gabon margin is interpreted to have occurred during an interval straddling the Early-Late Aptian boundary (∼118.4–116.8 Ma). These findings are comparable with other published estimates for salt deposition from northeast Brazil but differ from published estimates from the Campos-Santos basins; the latter are critically discussed. This study provides an important stratigraphic dataset for offshore Gabon and contributes to the ongoing debate regarding the timing of rifting and salt deposition in the Early Cretaceous of the South Atlantic passive margin system. Highlights: Early Cretaceous stratigraphic framework, offshore Gabon, constraining the timing of margin evolution and salt deposition Multi-disciplinary dataset including stable isotopes, palynological and ostracod biostratigraphy and sequence stratigraphy. Valanginian Weissert event and Early Aptian d 13 C event(s) identified in the Pre-Salt sequence. Salt deposition on the Gabon margin is interpreted to have occurred during the Early-Late Aptian (∼118.4 to 116.8 Ma). Other published estimates for the timing of salt deposition in the South Atlantic are critically assessed and evaluated.